Painting Women Cosmetics, Canvases, and Early Modern Culture - Phillippy, Patricia (Johns Hopkins University Press, 2006)
This original analysis of the representation and self-representation of women in literature and visual arts revolves around multiple early modern senses of "painting": the creation of visual art in the form of paint on canvas and the use of cosmetics to paint women's bodies. Situating her study in sixteenth- and seventeenth-century Italy, France, and England, Patricia Phillippy brings together three distinct actors: women who paint themselves with cosmetics, women who paint on canvas, and women and men who paint women-either with pigment or with words. Phillippy asserts that early modern attitudes toward painting, cosmetics, and poetry emerge from and respond to a common cultural history. Materially, she connects those who created images of women with pigment to those who applied cosmetics to their own bodies through similar mediums, tools, techniques, and exposure to toxic materials. Discursively, she illuminates historical and social issues such as gender and morality with the nexus of painting, painted women, and women painters.Teasing out the intricate relationships between these activities as carried out by women and their visual and literary representation by women and by men, Phillippy aims to reveal the delineation and transgression of women's creative roles, both artistic and biological. In Painting Women, Phillippy provides a cross-disciplinary study of women as objects and agents of painting.